INNOVATING CUSTOMS PRACTICES FOR CROSS-BORDER E-COMMERCE: CAMBODIA’S EXPERIENCE AND WAY FORWARD - angkearsoben tan (JURNAL PERSPEKTIF BEA DAN CUKAI, 2025)
Cross-border e-commerce has created new momentum for Cambodia’s trade growth, bringing both opportunities and challenges for the General Department of Customs and Excise of Cambodia (GDCE). As the volume of low-value shipments continues to rise, the GDCE has taken progressive steps to modernize its systems and strengthen compliance while supporting trade facilitation. Building on ongoing reforms, including the Strategy for Customs Reform and Modernization and the adoption of electronic data exchange systems, Cambodia is moving toward greater alignment with the WCO Framework of Standards on Cross-Border E-Commerce. These efforts reflect the GDCE’s readiness to apply innovation, data analytics, and partnership-based approaches to ensure efficient, transparent, and secure cross-border trade. Keywords: E-Commerce, Customs, Control, Cambodia, Revenue, WCO, Standards